Lysophosphatidylcholine aggravates contact hypersensitivity by promoting neutrophil infiltration and IL17 expression - Song, Mi Hye (BMB Rep, 2021)
Lysophosphatidylcholine (LPC) is a bioactive lysolipid known to contribute to the development of lung allergic diseases. However, it remains unknown whether LPC possesses proinflammatory properties in the skin as well. Here, we investigated this issue by injection of LPC into the murine contact hypersensiti-vity (CHS) model induced by 2,4-dinitrofluorobenzene (DNFB). LPC increased the expression of IL17, recruited more neutrophils, and eventually aggravated the CHS in the skins. Moreover, the effects of LPC diminished after neutralizing IL17 or depleting neutrophils. Mechanistically, LPC upregulated not only IL17 but also CXCL1 and CXCL2 in a G2A-dependent manner. Taken together, our study demonstrated that the upregulation of LPC could contribute to allergic skin inflammation by increasing IL17 expression and neutrophil recruitment via G2A receptor.